Pengaruh Perceived Quality, Brand Loyalty, Price Fairness, Satisfaction Terhadap Repurchase Intention Pada UKM Bakery di Jawa Tengah - Agus, Gregorius Marcelino (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
The purpose of this study was to determine the effect of Perceived Quality, Brand Loyalty, Price Fairness, Customer Satisfaction Toward Repurchase Intention on SMEs CV. Mitra Pangan in Central Java. The data analysis tool used is multiple regression with SPSS software. Data were collected using a questionnaire distributed to 200 consumers of Cocola sweet bread which is a product of CV. Mitra Pangan. The results showed that Perceived Quality, Brand Loyalty, Price Fairness, Customer Satisfaction had a positive effect on Repurchase Intention.